Continued survival of the Asiatic black bear Ursus thibetanus in Hainan, China - Jialing Li; Yilin Cui; Hui Liu; Youqiang Wang; Heidi Ma; Samuel T. Turvey (Oryx)
Determining whether cryptic remnant animal populations survive within specific landscapes is a conservation challenge and may require multiple types of information. Hainan Island, China, has lost most of its large mammal fauna, with no recent evidence for persistence of large carnivores. We conducted a survey of local ecological knowledge in communities around seven protected areas in 2015, collecting sighting reports of the Asiatic black bear Ursus thibetanus. Respondents living near Wuzhishan National Nature Reserve reported the highest number of dated sightings as well as the most recent sightings. In follow-up interviews, wildlife rangers at Wuzhishan reported recent signs of bears and local hunting, and a possible bear photograph was taken inside the Reserve in 2017. Characteristic bear signs, including fresh diagnostic claw marks on trees, were detected at Wuzhishan in 2021, confirming bear presence. Wuzhishan is the last area in Hainan where large herbivores and carnivores survive, and where local conservation efforts still have the potential to maintain functional forest ecosystems that support megafaunal assemblages.